Shorter and Warmer Winters Expand the Hibernation Area of Bats in Europe - Kseniia Kravchenko; Christian C. Voigt; Jan Volkholz; Alexandre Courtiol; Shannon E. Currie (Ecology Letters, 2025)
Predicting species range shifts in response to environmental change requires the determination of regions where individuals maintain a positive energy budget. For hibernating animals, this budget depends on two physiological states (normothermy and torpor) that alternate in response to ambient temperature. To study range shifts of hibernators like the common noctule ( Nyctalus noctula ), we developed an ecophysiological approach that integrates metabolic rates, physiological states, and environmental conditions. Our model accurately hindcasted the northward range shift of this migratory bat over the past 50 years. Under climate change forecasts SSP1‐2.6, SSP2‐4.5, SSP3‐7.0, and SSP5‐8.5, for which winters will shorten by 1.4–41 days and warm by 0.11°C–2.3°C, the hibernation area is predicted to shift by 78–732 km and expand north‐eastward by 5.8%–14% by 2100. Mean ambient temperature and winter duration prove sufficient to approximate the hibernation niche and may be used to predict changes in hibernation areas where collecting physiological measurements is difficult.

Monitoring terrestrial wildlife by combining hybridization capture and metabarcoding data from waterhole environmental DNA - Juan Li; Peter Seeber; Jan Axtner; Rachel Crouthers; Milou Groenenberg; Arnulf Koehncke; Alexandre Courtiol; Pin Chanratana; Alex D. Greenwood (Biological Conservation, 2023)

Sex‐specific spatial variation in fitness in the highly dimorphic Leucadendron rubrum - Jeanne Tonnabel; Etienne K. Klein; Ophélie Ronce; Sylvie Oddou‐Muratorio; François Rousset; Isabelle Olivieri; Alexandre Courtiol; Agnès Mignot (Molecular Ecology, 2021)
Sexual dimorphism in plants may emerge as a result of sex‐specific selection on traits enhancing access to nutritive resources and/or to sexual partners. Here we investigated sex‐specific differences in selection of sexually dimorphic traits and in the spatial distribution of effective fecundity (our fitness proxy) in a highly dimorphic dioecious wind‐pollinated shrub, Leucadendron rubrum . In particular, we tested for the effect of density on male and female effective fecundity. We used spatial and genotypic data of parent and offspring cohorts to jointly estimate individual male and female effective fecundity on the one hand and pollen and seed dispersal kernels on the other hand. This methodology was adapted to the case of dioecious species. Explicitly modelling dispersal avoids the confounding effects of heterogeneous spatial distribution of mates and sampled seedlings on the estimation of effective fecundity. We also estimated selection gradients on plant traits while modelling sex‐specific spatial autocorrelation in fecundity. Males exhibited spatial autocorrelation in effective fecundity at a smaller scale than females. A higher local density of plants was associated with lower effective fecundity in males but was not related to female effective fecundity. These results suggest sex‐specific sensitivities to environmental heterogeneity in L. rubrum . Despite these sexual differences, we found directional selection for wider canopies and smaller leaves in both sexes, and no sexually antagonistic selection on strongly dimorphic traits in L. rubrum . Many empirical studies in animals similarly failed to detect sexually antagonistic selection in species expressing strong sexual dimorphism, and we discuss reasons explaining this common pattern.

Fragmentation of lead-free and lead-based hunting rifle bullets under real life hunting conditions in Germany - Anna Lena Trinogga; Alexandre Courtiol; Oliver Krone (Ambio, 2019)

Effects of remarriage after widowhood on long-term fitness in a monogamous historical human population - Jenni E Pettay; Anna Rotkirch; Alexandre Courtiol; Markus Jokela; Virpi Lummaa (Behavioral Ecology and Sociobiology, 2014)

Climatic variation and age‐specific survival in Asian elephants from Myanmar - Hannah S. Mumby; Alexandre Courtiol; Khyne U. Mar; Virpi Lummaa (Ecology, 2013)
Concern about climate change has intensified interest in understanding how climatic variability affects animal life histories. Despite such effects being potentially most dramatic in large, long‐lived, and slowly reproducing terrestrial mammals, little is known of the effects of climatic variation on survival in those species. Asian elephants ( Elephas maximus ) are endangered across their distribution, and inhabit regions characterized by high seasonality of temperature and rainfall. We investigated the effects of monthly climatic variation on survival and causes of death in Asian elephants using a unique demographic data set of 1024 semi‐captive, longitudinally monitored elephants from four sites in Myanmar between 1965 and 2000. Temperature had a significant effect on survival in both sexes and across all ages. For elephants between 1 month and 17 years of age, maximal survival was reached at ∼24°C, and any departures from this temperature increased mortality, whereas neonates and mature elephants had maximal survival at even lower temperatures. Although males experienced higher mortality overall, sex differences in these optimal temperatures were small. Because the elephants spent more time during a year in temperatures above 24°C than in temperatures below it, most deaths occurred at hot (temperatures >24°C) rather than cold periods. Decreased survival at higher temperatures resulted partially from increased deaths from infectious disease and heat stroke, whereas the lower survival in the coldest months was associated with an increase in noninfectious diseases and poor health in general. Survival was also related to rainfall, with the highest survival rates during the wettest months for all ages and sexes. Our results show that even the normal‐range monsoon variation in climate can exert a large impact on elephant survival in Myanmar, leading to extensive absolute differences in mortality; switching from favorable to unfavorable climatic conditions within average years doubled the odds for mortality. The persistence of a long‐term trend toward higher global temperatures, combined with the possibility of higher variation in temperature between seasons, may pose a challenge to the survival of species such as Asian elephants.